Dampak Pembangunan Sektor Pertanian Terhadap Perekonomian di Desa Palsabolas Kecamatan Angkola Timur Kabupaten Tapanuli Selatan - Juwita Handayani; Fakhrurrozi; Arsidin Batubara; Edison Siregar; Imelda Martauli Pardede (INDO PUBLISHING, 2025)
The purpose of this study is to determine the impact of agricultural sector development on the economy in Palsabolas Village, East Angkola District, South Tapanuli Regency. The population in this study was Palsabolas Village, which consists of six hamlets. Data collection techniques were conducted directly in the field using several primary data collection techniques. Therefore, based on the research results obtained through qualitative analysis, it indicates that the agricultural sector has a positive and significant influence on the economic growth of Palasabolas Village, East Angkola District, South Tapanuli Regency. This is indicated by the t-test, which has a significance value of less than 0.05 or a significance value of 0.000 <0.05. Limitations and shortcomings in this study are unavoidable. Therefore, existing limitations may result in research results that do not accurately reflect the true situation. Researchers cannot reliably determine the accuracy of the information or data provided by respondents, particularly personal information such as education level, age, and family income. For various reasons, not all respondents in Palsabolas Village, East Angkola District, were willing to participate in this study. Therefore, programs in economic sectors, particularly the agricultural sector, need to be further enhanced as an effort to boost economic growth. This also includes preserving existing natural resources so they can be processed and generate benefits for the community.